Problems in Learning “Telaah Teks Inggris IQT”: An Investigation of Foreign Language Acquisition - Sri Nurhayati (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2018)
This study is trying to convey, describe and look for the solution on the students of Ilmu Al-Qur’an and Tafsir problems on the “Telaah Teks Inggris IQT” class. This study was conducted in STAIN Pamekasan with respondents from students of Ilmual_Qur’an and Tafsir. This study is a descriptive qualitative research. The data is taken through observation, interview and documentation. The result of this research show that the students’ background knowledge, either their knowledge on Islamic education or English, influence the process of interpreting the English text. These differences also influence their motivation in learning English. Another factor affecting the students’ competence is the hoterogenousity of the students’ characteristics which often lead to problems. After identifying all problems faced by the students of Ilmu Al-Qur’an and Tafsir, the lecturer can formulate the best technique in teaching English especially for Telaah Teks Inggris class where English is their second/ foreign language.